2019
DOI: 10.1136/thoraxjnl-2018-211516
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stress-induced mast cell degranulation activates TGF-β1 signalling pathway in pulmonary fibrosis

Abstract: BackgroundThe role of mast cells accumulating in idiopathic pulmonary fibrosis (IPF) lungs is unknown.ObjectivesWe investigated the effect of fibrotic extracellular matrix (ECM) on mast cells in experimental and human pulmonary fibrosis.ResultsIn IPF lungs, mast cell numbers were increased and correlated with disease severity (control vs 60%90% vs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 41 publications
2
59
2
1
Order By: Relevance
“…In the pathological state of ARDS, different mechanical stretch modes and amplitudes have different molecular biological and cytological effects on lung tissue cells, affecting gene expression and metabolism of cells. Biomechanical signal transduction has a key role in the initiation of mechanical activation of intracellular inflammatory signaling pathways (15). During the mechanical ventilation treatment of ARDS, the connective tissue of the lung continuously withstands and transmits mechanical signals.…”
Section: Discussionmentioning
confidence: 99%
“…In the pathological state of ARDS, different mechanical stretch modes and amplitudes have different molecular biological and cytological effects on lung tissue cells, affecting gene expression and metabolism of cells. Biomechanical signal transduction has a key role in the initiation of mechanical activation of intracellular inflammatory signaling pathways (15). During the mechanical ventilation treatment of ARDS, the connective tissue of the lung continuously withstands and transmits mechanical signals.…”
Section: Discussionmentioning
confidence: 99%
“…20 Andersson and colleagues provide evidence for a switch to the connective tissue MC subtype expressing both chymase and tryptase proteases (MC TC ) in IPF lung, 24 and this increase in MC TC s in IPF has been confirmed recently. 20 In contrast, Cha and colleagues propose a protective role for lung MCs since patients with higher numbers of these cells had less decline in lung function. 16 Stem cell factor (SCF) is a key survival factor for mast cells, acting through the tyrosine kinase receptor ckit (also known as CD117 or SCF receptor).…”
Section: Why Read On?mentioning
confidence: 93%
“…Several studies have shown that MCs and their mediators, such as histamine, are increased in lung tissue and bronchoalveolar lavage from patients with IPF. [14][15][16][17][18][19][20] What is the bottom line?…”
Section: Introductionmentioning
confidence: 99%
“…The severity of lung fibrosis was scored on a scale from 0 to 8 as already published [ 19 ]. Lung sections were stained with toluidine blue to enumerate mast cells [ 35 ].…”
Section: Methodsmentioning
confidence: 99%